Influence of an ultrasonic nozzle in spray-drying and storage on the properties of blueberry powder and microcapsules - Turan, Feyza Tatar; Cengiz, Alime; Sandikci, Dilara; Dervisoglu, Muhammet; Kahyaoglu, Talip (WILEY, 2016)
BACKGROUNDRecently, ultrasonic nozzle technology has been applied in spray-drying because of its numerous advantages, including providing more uniform droplets and reducing damage observed in bioactive compounds. In this study, the production of blueberry powders and microcapsules by using an ultrasonic spray nozzle was investigated. Firstly, the important ultrasonic nozzle parameters were optimised by using response surface methodology and compared with a conventional nozzle (control). Secondly, powder and microcapsules obtained at the optimum point were stored at 22 degrees C and 35 degrees C at 0.32 water activity (a(w)). RESULTSThe optimum conditions were estimated as 125 degrees C inlet air temperature, 9W ultrasonic power and 8% feed pump rate. There was significantly difference (P < 0.05) in the total phenolic content and antioxidant power of microcapsules produced by an ultrasonic nozzle and a conventional nozzle. Because the temperature affected the stability of powders negatively, the blueberry powder showed higher losses than microcapsules in the content of bioactive compounds. In addition, the ultrasonic nozzle showed a significantly greater protective effect on physico-chemical properties than did the conventional nozzle. CONCLUSIONResults of the study point that the production of ultrasonic nozzle powders and microcapsules is feasible to use as a functional ingredient in food industry. (c) 2016 Society of Chemical Industry
Keywords: anthocyanins; micro-encapsulation; spray-drying; storage stability; POMEGRANATE PUNICA-GRANATUM; PHYSICOCHEMICAL PROPERTIES; ANTIOXIDANT CAPACITY; MICROENCAPSULATION; STABILITY; ATOMIZATION; PHENOLICS; PROTEIN; GUM; Agriculture; Chemistry; Food Science & Technology